Implementasi Pendidikan Agama Islam di Masa Pandemi Covid-19 - Muhammad Yusuf; Hamdani Hamdani; Annisa Putri Siregar; Fatin Nadia Siregar (Maslahah: Jurnal Pengabdian Masyarakat, 2020)
The hard work of the teaching staff so far really must be appreciated. Because in the midst of social restrictions due to the 19th plague, we are still interested in teaching and pursuing knowledge, almost no one thought, the face of education would change drastically due to the covid-19 outbreak. To break the spread of this epidemic, the government is making a change from formal education in school to learning from home, with an online system.This research is a research study conducted online as well, with 3 men and 6 women interviewed. Technical analysis of the data used interviews. Based on the results of these studies it can be stated that with the application of education in the co-19 pandemic period is using online or online learning, which has advantages and disadvantages. Keywords : Education, Islamic Religious Education, and Covid 19